2017
DOI: 10.1051/0004-6361/201628620
|View full text |Cite
|
Sign up to set email alerts
|

Results from a triple chord stellar occultation and far-infrared photometry of the trans-Neptunian object (229762) 2007 UK126

Abstract: Context.A stellar occultation by a trans-Neptunian object (TNO) provides an opportunity to probe the size and shape of these distant solar system bodies. In the past seven years, several occultations by TNOs have been observed, but mostly from a single location. Only very few TNOs have been sampled simultaneously from multiple locations. Sufficient data that enable a robust estimation of shadow size through an ellipse fit could only be obtained for two objects. Aims. We present the first observation of an occu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…Recent works with this TPM code (e.g. Pál et al 2015Pál et al , 2016Schindler et al 2017;Fornasier et al 2013) have shown that a combined analysis of Herschel and Spitzer thermal measurements enable us to constrain the spin-axis orientation of TNOs. Following up on this expertise, we also applied this code in the case of 2003 AZ 84 , assuming a spherical shape model and a constant emissivity of 0.9 at all MIPS and PACS wavelengths (emissivity effects are only expected at longer wavelengths, see Fornasier et al 2013).…”
Section: Analysis Of 2003 Az 84 Resultsmentioning
confidence: 99%
“…Recent works with this TPM code (e.g. Pál et al 2015Pál et al , 2016Schindler et al 2017;Fornasier et al 2013) have shown that a combined analysis of Herschel and Spitzer thermal measurements enable us to constrain the spin-axis orientation of TNOs. Following up on this expertise, we also applied this code in the case of 2003 AZ 84 , assuming a spherical shape model and a constant emissivity of 0.9 at all MIPS and PACS wavelengths (emissivity effects are only expected at longer wavelengths, see Fornasier et al 2013).…”
Section: Analysis Of 2003 Az 84 Resultsmentioning
confidence: 99%
“…Considering this, we also plot all known objects. The observed population is taken from the Minor Planet Center (on 10th October 2017), with measured radii from occulations (Elliot et al 2010;Sicardy et al 2011;Braga-Ribas et al 2013;Alvarez-Candal et al 2014;Dias-Oliveira et al 2017;Schindler et al 2017), direct imaging (Nimmo et al 2017), thermal modelling (Lim et al 2010;Müller et al 2010;Mommert et al 2012;Pál et al 2012;Santos-Sanz et al 2012;Vilenius et al 2012;Fornasier et al 2013;Lellouch et al 2013;Vilenius et al 2014), or by assuming albedos of (D/250 km) 2 + 6 % per Fraser et al (2014), in that order of priority. Masses for objects with satellites were taken from Benecchi et al (2010); Brown (2013); Brown & Schaller (2007); Carry et al (2011);Fraser et al (2013); Grundy et al (2007Grundy et al ( , 2008Grundy et al ( , 2009Grundy et al ( , 2011Grundy et al ( , 2012Grundy et al ( , 2015; Kovalenko et al (2017); Margot et al (2004); Parker et al (2011); Ragozzine & Brown (2009);Sheppard, Ragozzine & Trujillo (2012); Stansberry et al (2012); Stern et al (2015); Veillet et al (2002).…”
Section: Observations and Our Inferences Of The Pastmentioning
confidence: 99%
“…Our analysis is based on the data obtained during the "TNOs are cool" program, which contains 28 binary and 2 triple systems A&A 608, A19 (2017) Schindler et al (2017) 3.79 --…”
Section: Datasetmentioning
confidence: 99%